Authorship Trends of Research Articles Published in Seven Scientific, Technical, Engineering, and Medical (STEM) Library Journals: Analysis of STEM Library Research from 2016 to 2019 Update. Issue 2 (3rd April 2021) - Aytac, Selenay; Tran, Clara Y.
ABSTRACT: Authorship patterns of research articles published in seven Scientific, Technical, Engineering, and Medical (STEM) library science journals have been examined previously for the five years from 2011 to 2015 by using bibliometric techniques. This study has now been updated for the years from 2016 to 2019 by analyzing 590 research articles. The same journals: Science & Technology Libraries, Issues in Science & Technology Librarianship, Journal of eScience Librarianship, Journal of Hospital Librarianship, Journal of the Medical Library Association, Medical Reference Services Quarterly, and Health Information and Libraries Journal, were studied. Some of the variables we have examined in both samples include (1) authorship, (2) affiliation, (3) country of origin, and (4) topic of the research articles. The findings presented a unique opportunity to determine the current state of art in STEM librarianship research by using the most recent data gathered from seven prominent STEM library science journals.